2007
DOI: 10.1111/j.1365-2796.2007.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptors – from active regulators of macrophage biology to pharmacological targets in the treatment of cardiovascular disease

Abstract: Altered macrophage functions contribute to the pathogenesis of many infectious, immunological and inflammatory disease processes. Pharmacological modulation of macrophage activities therefore represents an important strategy for the prevention and treatment of inflammation-related diseases, such as atherosclerosis. This review focuses on recent advances on the role of the peroxisome proliferatoractivated receptor transcription factor family in the modulation of lipid homeostasis and the inflammatory response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 138 publications
2
39
0
Order By: Relevance
“…In particular, pro-inflammatory M1 and anti-inflammatory M2 macrophage phenotypes could influence the development of atherosclerosis. Interestingly, M1-and M2-like macrophages coexist in atheroma (Bouhlel et al, 2008;Curtiss and Tobias, 2009), which suggests the n-3 PUFA-induced M2 polarization of macrophages in atheroma might delay the progress of atherosclerosis and subsequent cardiovascular diseases. In a mouse model, dietary n-3 polyunsaturated fatty acids (menhaden oil) prevented the development of atherosclerotic lesions by a saturated fat diet (palm oil plus cholesterol) in mice (Renier et al, 1993), and in a recent study, it was concluded that polyunsaturated fat intake is associated with a lower risk of fatal coronary heart disease in men (Virtanen et al, 2014).…”
Section: Functions Of Ffa4 In Other Macrophagesmentioning
confidence: 97%
“…In particular, pro-inflammatory M1 and anti-inflammatory M2 macrophage phenotypes could influence the development of atherosclerosis. Interestingly, M1-and M2-like macrophages coexist in atheroma (Bouhlel et al, 2008;Curtiss and Tobias, 2009), which suggests the n-3 PUFA-induced M2 polarization of macrophages in atheroma might delay the progress of atherosclerosis and subsequent cardiovascular diseases. In a mouse model, dietary n-3 polyunsaturated fatty acids (menhaden oil) prevented the development of atherosclerotic lesions by a saturated fat diet (palm oil plus cholesterol) in mice (Renier et al, 1993), and in a recent study, it was concluded that polyunsaturated fat intake is associated with a lower risk of fatal coronary heart disease in men (Virtanen et al, 2014).…”
Section: Functions Of Ffa4 In Other Macrophagesmentioning
confidence: 97%
“…PPAR-α activation can also have direct antiatherogenic effects on the different cell types of the vascular wall by decreasing the expression of adhesion molecules, tissue factor, interleukin-6 (IL-6), and endothelin-1 (Israelian- Konaraki and Reaven, 2005). The latest evidence describing how PPAR transcription factors may modulate different steps of atherosclerosis development and progression and the therapeutical potential of PPAR ligands have been recently reviewed elsewhere (Bouhlel et al, 2008).…”
Section: Molecular Mechanisms Regula-ting Enosmentioning
confidence: 98%
“…12 More specifically, PPARγ activation enhances the alternative (M2) activation/differentiation of macrophages with expression of anti-inflammatory markers, such as CD206 (mannose receptor) and CD36 (a member of the class B scavenger receptor family). 14,15 In an animal study, it was reported that oral administration of pioglitazone reduced macrophage content and matrix metalloproteinase (MMP) activity in murine carotid atherosclerosis. 16 Several clinical studies have also suggested the atheroprotective effects of pioglitazone.…”
mentioning
confidence: 99%